The Prevalence of feeding disorders in healthy infants and children under 3 years of age based on a questionnaire study - Aleksandra Kamińska-Sobczak; Elżbieta Trafalska; Ewelina Gaszyńska (Kazimierz Wielki University, 2023)
Introduction and purpose Depending on the source, feeding disorders are common reasons to visit a pediatrician - reported in 2-60% of generally healthy children. This study was designed in order to assess the incidence of feeding difficulties in a group of healthy children aged 6-36 months from the Łódź region and to identify factors that may be related to feeding disorders. Material and method The research tool of this study was a questionnaire designed by the authors which consisted of 4 personal data questions, 9 questions about the perinatal and neonatal period, 36 feeding questions, 10 questions about child development and weight gain, 10 questions about previous medical history, 30 questions about symptoms, 8 questions about misbehavior during feeding and 14 sociodemographic questions. Results 215 parents completed questionnaires. However, 10 of them were rejected because those participants met the exclusion criteria. Finally, 205 children were enrolled in the study. The difficulties in feeding were confirmed by the parents of 66 participants. Children with feeding difficulties were more often attended to specialist ambulatories, had been diagnosed with food allergies, and underwent speech therapy and rehabilitation. Additionally, the analysis showed that feeding disorders in mothers and the occurrence of stressful situations in the family were more frequent in children whose parents reported feeding difficulties. Conclusions The incidence of feeding difficulties, in the group of healthy children aged 6-36 months from the Łódź region, was higher than reported in other studies. Therefore there is an urgent need to educate parents on feeding recommendations to modify eating behaviors and overcome feeding disorders, followed by some practical advice on appropriate diet adjustment.